1996
DOI: 10.5032/jae.1996.03033
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of University of Illinois College of Agriculture Freshmen Toward Agriculture

Abstract: The primary purpose of this study was to determine the attitudes and intentions of University of Illinois College of Agriculture freshmen toward high school and university agriculture programs and the field of agriculture in an effort to better identify, recruit, and retain students in the College. Results indicated that a majority of freshmen students were female, Caucasian, had no background in agriculture, and viewed agriculture as being both scientific and technical. Students also believed high school agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 0 publications
3
29
1
1
Order By: Relevance
“…For example, the lack of adequate high school agriculture enrollment can translate at the post-secondary level into fewer students with agricultural training entering colleges of agriculture (Dyer & Breja, 2003). Additionally, low enrollments can result in colleges that are unable to recruit and retain students with agricultural backgrounds which translate into the loss of millions of dollars for universities (Dyer, Lacey, & Osborne, 1997). Decreased enrollments at the secondary level can also affect the supply and demand for agriculture teachers as well as other areas of the agriculture industry.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the lack of adequate high school agriculture enrollment can translate at the post-secondary level into fewer students with agricultural training entering colleges of agriculture (Dyer & Breja, 2003). Additionally, low enrollments can result in colleges that are unable to recruit and retain students with agricultural backgrounds which translate into the loss of millions of dollars for universities (Dyer, Lacey, & Osborne, 1997). Decreased enrollments at the secondary level can also affect the supply and demand for agriculture teachers as well as other areas of the agriculture industry.…”
Section: Introductionmentioning
confidence: 99%
“…The project's research team identified questionnaire items used in previous studies with similar purposes (Cecchettini, Sommer, & Leising, 1992;Dyer, Breja, & Andreasen, 1999;Dyer, Lacey, & Osborne, 1996;Faulkner, Baggett, Bowen, & Bowen, 2009;Wildman & Torres, 2001) The questionnaire was field-tested with a similar population of students from a different high school and found to be reliable ( = .70).…”
Section: Hsai Questionnairementioning
confidence: 99%
“…Suggested variables include learning style (field‐independent, field‐dependent, field‐neutral), critical thinking disposition, class attendance (Fidanza, 2006), work ethic, study habits, emotional state, socioeconomic status, extracurricular activities, and classification. Participation in 4‐H/FFA activities should also be included in product variable inquiry of post‐secondary agricultural education settings (Ball et al, 2001; Dyer et al, 1996; Dyer and Breja, 1999). These variables could potentially be used by instructors to identify potential unsatisfactory and satisfactory outcomes in agricultural courses.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%